Use of methyl methacrylate, moulded in its paste phase, to fill the orbital cavity of dogs, after exenteration in cases of ophthalmic neoplasias: a report of three cases - Talieri, Ivia Carmem [UNESP]; Buquera, Luiz Eduardo Carvalho [UNESP]; Oriá, Arianne Pontes [UNESP]; Brunelli, Adriana Torrecilhas Jorge [UNESP]; Almeida, Denise Eliza De [UNESP]; Laus, José Luiz [UNESP] (Universidade Federal de Santa Maria, 2004)
Methyl methacrylate, acrylic resine for odontologic use, was used to fill the orbital cavity of three dogs which presented retrobulbar, eyeball and eyelid neoplasias extended to the orbital space, respectively. The material was moulded in the orbit before polymerization, while still in its paste phase. In each case, follow-up reports were obtained in the 10th and 40th days and in 18 months after surgery. Complications were not observed and improvement of cosmetic appearance was obtained.

O metilmetacrilato, resina acrílica de uso odontológico, foi empregado no preenchimento da cavidade orbitária de três cães, acometidos, respectivamente, por neoplasia retrobulbar, neoplasia do bulbo do olho e neoplasia palpebral com extensão para a órbita. O material foi moldado à órbita, ainda na fase pastosa da auto-polimerização. Em todos os casos, o acompanhamento se deu ao 10º e 40º dias e aos 18 meses após a cirurgia. Complicações não foram observadas e efeitos plásticos foram obtidos.
Uso do metilmetacrilato, moldado em fase pastosa, no preenchimento da cavidade orbitária de cães submetidos à exenteração, em casos de neoplasias oftálmicas: relato de três casos
Keywords: methyl methacrylate; prosthesis; orbit; neoplasia; dogs; metilmetacrilato; prótese; órbita; neoplasia; cães